Peningkatan Hasil Belajar Siswa pada Mata Pelajaran IPS melalui Penerapan Model Role-Playing di Kelas V SDN Jarin 4 Kecamatan Pademawu Kabupaten Pamekasan Tahun Pelajaran 2018/2019 - Sunarto Sunarto (Departement of Mathematics Education, 2023)
Developing the abilities of students is one of the tasks for teachers which can be said to be a task that is not easy. Before teaching the teacher should know in advance the abilities of each student, after that the teacher compiles what actions will be carried out in the planning, implementation and assessment stages of learning. This study aims to determine the increase in learning outcomes through the Role-Playing Model in Social Studies subjects in Class V. The application of role-playing models in Social Studies subjects is proven to improve learning outcomes, however this learning has weaknesses, namely the level of understanding of students is different and requires long time. In cycle I, student learning outcomes increased from learning outcomes in pre-action, which was originally 7 students (25%) to 8 students (28.57%) and experienced another increase in cycle II to 17 students (60.71%).